War Within : America's Battle Over Vietnam - Wells, Tom (Open Road Distribution, 2016)
The War Within: America's Battle over Vietnam is a painfully engrossing and popularly written account of how the battle on the home front ended America's least popular war. This absorbing narrative, hailed by critics of every persuasion, is the fruit of over a decade's worth of research: the author sifted through mountains of government documents, press coverage, and transcripts of interviews he conducted with virtually all of the key players, both inside the U.S. government and among the dissenters who eventually brought the war to an end. In these pages the antiwar era comes to life through the words of scores of participants, both the famous and the forgotten, who speak with candor and passion about this tumultuous period. A remarkable story of a powerful grassroots movement and its influence on officials in Washington.